Comparative analysis of the related interests of relevant stakeholders in the development of seaports in relation to the spatial concept of the city - Schiozzi, Donald (Array, 2018)
The seaport, as a link of the transport chain, is oriented towards the development of the maritime system of the country and the summit place of traffic slope from all transport routes and means of transport. While the city, as a community of residents, is oriented towards promoting the well-being of citizens and the quality of their lives, so it strives to ecological, cultural and visual values. This relation of interest is merely one of the numerous relations of interest of the relevant stakeholders in the planning and development of the seeports in relation to the spatial concept of cities deriving from a constrained coexistence in a restricted area – as two separate entities whose interests and objectives appear to be different at first sight. In this paper, the relations of interest of the relevant stakeholders have been analyzed, quantitative and qualitative variables have been evaluated that influence the development of the seaports in relation to the spatial concept of the city. The research has highlighted the need to look at and analyze all relevant stakeholders interests, of which the most important are: state – local community, state – managing body of the port, state – economy, local community – managing body of the port, local community – economy and economy – managing body of the port.